Phospholipid–Detergent Conjugates as Novel Tools for siRNA Delivery. Issue 7 (7th January 2013) - Pierrat, Philippe; Laverny, Gilles; Creusat, Gaëlle; Wehrung, Patrick; Strub, Jean‐Marc; VanDorsselaer, Alain; Pons, Françoise; Zuber, Guy; Lebeau, Luc
Abstract One of the potential benefits of drug delivery systems in medicine is the creation of nanoparticle‐based vectors that deliver a therapeutic cargo in sufficient quantity to a target site to enable a selective effect, width of the therapeutic window depending on the toxicity of the vector and the cargo. In this work, we intended to improve the siRNA delivery efficiency of a new kind of nucleic acid carrier, which is the result of the conjugation of the membrane phospholipid 1, 2‐dioleoyl‐sn‐glycero‐3‐phosphocholine (DOPC) to the membrane‐active species Triton X‐100 (TX100). We hypothesized that by improving the biodegradability the cytotoxicity of the conjugate might by reduced, whereas its original transfection potential would be tentatively preserved. DOPC was conjugated to Triton X‐100 through spacers displaying various resistance to chemical hydrolysis and enzyme degradation. The results obtained through in vitro siRNA delivery experiments showed that the initial phosphoester bond can be replaced with a phospho(alkyl)enecarbonate group with no loss in the transfection activity, whereas the associated cytotoxicity was significantly decreased, as assessed by metabolic activity and membrane integrity measurements. The toxicity of the conjugates incorporating a phospho(alkyl)enesuccinnate moiety proved even lower but was clearly balanced with a reduction of the siRNA delivery efficiency. Hydrolytic stability and intracellular degradation of the conjugates were investigated by NMR spectroscopy and mass spectrometry. A general trend was that the more readily degraded conjugates were those with the lower toxicity. Otherwise, the phospho(alkyl)enecarbonate conjugates revealed some hemolytic activity, whereas the parent phosphoester did not. The reason why these conjugates behave differently with respect to hemolysis might be a consequence of unusual fusogenic properties and probably reflects the difference in the stability of the conjugates in the intracellular environment.